A dictionary of locutions from liturgical books by protopriest A. I. Nevostruev (мѵро-мѵрсiнѡръ; набдѣваю-напрасный) - Maria Davydenkova; Nadezhda Kaluzhnina; Olga Strievskaya; Natalia Mazurina; Maria Strievskaya (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ III. Filologiâ, 2019)
The Dictionary of Locutions from Liturgical Books by Protopriest A. Nevostruev, completed in the middle of the 19th century and never published, can be regarded both as a signifi cant achievement of Church Slavonic studies and as a valuable lexicographic source. The manuscript is kept in the Russian State Library. The decrepit state of the manuscript has determined the necessity of its urgent study and edition. The signifi cance of this project is primarily due to the fact that the text of the dictionary is being made accessible to linguists for the fi rst time. The orthography and grammar of the dictionary reflect the linguistic views of the time of its creation and can be of interest for those who study the history of Russian linguistics. This paper contains another part of dictionary entries beginning in letters M and N. The characteristic features of the publication of this Dictionary, the lists of sources, abbreviations and symbols were described in detail in the previous issues of St. Tikhon’s University Review. All previously published parts of the Dictionary together with the critical apparatus can be found at the website of the Faculty of Philology at St. Tikhon’s University for the Humanities: http://pstgu.ru/faculties/philological/science/slov_Nevostr/